2012
DOI: 10.2138/am.2012.4086
|View full text |Cite
|
Sign up to set email alerts
|

Metastable equilibrium in the C-H-O system: Graphite deposition in crustal fluids

Abstract: The presence of graphite in natural environments is linked to the redox and thermal conditions of C-H-O fluid/graphite equilibrium in hydrothermal veins and metasomatic contacts. A time-series experimental study was performed to investigate the graphite undersaturated C-H-O system at 600 °C and 1000 MPa, and with f O2 ranging from highly reducing (10 −23 ) to highly oxidizing (10 4 ). A nonvolatile intermediate carbon phase exhibiting the Raman spectral features of poorly ordered graphite was formed as the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Twenty milliliters of gas were collected and injected into 25 ml stoppered borosilicate vials containing 4 ml of 6% (w/v) AgNO 3 , 25% (w/v) H 3 PO 4 and 20 ml Argon grade zero. The vials were pretreated by following protocols discussed elsewhere (Foustoukos, 2012). The precipitated Ag 2 S and gases in the headspace was measured and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty milliliters of gas were collected and injected into 25 ml stoppered borosilicate vials containing 4 ml of 6% (w/v) AgNO 3 , 25% (w/v) H 3 PO 4 and 20 ml Argon grade zero. The vials were pretreated by following protocols discussed elsewhere (Foustoukos, 2012). The precipitated Ag 2 S and gases in the headspace was measured and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…In slab rocks, carbon is present in a variety of forms, including carbonate minerals and organic matter, derived from altered oceanic crust and marine sediments. Part of the carbon originally present in crustal lithologies is liberated as CO 2 , during low-grade metamorphic decarbonation reactions (e.g., Kerrick and Connolly 2001), or fixed as graphite (Foustoukos 2012;Galvez et al 2013). At greater sub-arc depths, coupled thermal and thermodynamic models strongly suggest that carbonate minerals do not react with silicate phases liberating CO 2 , and are stable along most subduction geothermal gradients (Connolly 2005;Gorman et al 2006;Molina and Poli 2008).…”
Section: Carbonmentioning
confidence: 99%
“…1), may not be as rapidly reactive as the graphite employed in the experiments. Experimental studies performed at metamorphic conditions in the crust (up to 725 °C and 1 GPa) have indicated that disordered forms of graphite can persist metastably in contact with C-O-H fluids, at least on the timescales of the experiments (Ziegenbein and Johannes 1980;Pasteris and Chou 1998;Foustoukos 2012). Even if such metastable forms of graphite persist at the higher temperatures and longer residence times of the upper mantle, however, it is not likely to have a large impact on the speciation of carbon in fluids in equilibrium with the graphite, since the thermodynamic 1 Figure 2.…”
Section: Experimental Studies Of Hydrocarbons At Mantle Conditionsmentioning
confidence: 99%